An Uncommon and Severe Presentation of a Common Virus – A Case of Varicella Zoster Virus Pneumonia - Gorgulho, Cátia; Ribeiro, Joana Freitas; Adelino, Lara; Elias, Telma (Brazilian Journal of Case Reports, 2024)
Chickenpox is a maculovesicular-papular exanthematic disease caused by primary infection with varicella zoster virus (VZV) and pneumonia is one of its most severe complications, associated with significant morbidity and mortality. A 46-year-old male presented to the emergency department with fever, dyspnea, myalgia and asthenia for the past 24 hours. He had a pruritic maculovesiculo-papular rash on the trunk and scalp, evolving over 4 days, and his 5-year-old daughter had recently been diagnosed with chickenpox. Initial imaging revealed diffuse bilateral pulmonary infiltrates, raising suspicion of viral pneumonia. Based on clinical presentation, radiological findings and epidemiological link, aciclovir therapy was initiated. During the first 24 hours, the patient’s worsening hypoxemia and increased respiratory effort required intensive care unit admission for high-flow nasal cannula oxygen therapy. Polymerase chain reaction (PCR) testing for VZV of skin vesicles and respiratory secretions confirmed the diagnosis. The patient showed clinical improvement within 5 days and was discharged 10 days after admission. This case underscores the importance of high clinical suspicion for VZV pneumonia and prompt treatment. PCR testing remains the gold standard for diagnosis. Early recognition and treatment of VZV-related complications are essential to reduce mortality. High clinical suspicion and early treatment in patients with VZV infection can significantly reduce associated mortality. It is crucial to consider uncommon viruses that can cause severe respiratory infections, even in immunocompetent individuals.